Hypocaloric, plant-based oatmeal interventions in the treatment of poorly-controlled type 2 diabetes: A review. Issue 4 (December 2019) - Storz, Maximilian Andreas; Küster, Onno
Background: Lifestyle interventions, including dietary modifications, play a key role in the treatment of type 2 diabetes. By the second half of the last century, dietary oatmeal interventions had frequently been used in patients with diabetes; however, with the widespread introduction of insulin, this practice gradually fell into disuse. Within the last decades, the original oatmeal intervention, first described in 1903, has been modified towards a hypocaloric, low-fat, and plant-based intervention. Aim: The aim of this review was to investigate the current role of these adapted short-term dietary oatmeal interventions in the treatment of patients suffering from poorly-controlled type 2 diabetes. A special focus was put on opportunities for and barriers to its clinical implementation and its potential mechanisms of action. Methods: The electronic databases of PubMed and Google Scholar were searched using the keywords "oat, " "oats, " "oatmeal, " and "diabetes." Results: While there are a limited number of clinical studies including hypocaloric short-term dietary oatmeal interventions, there is evidence that these interventions may lead to a significant decrease in mean blood glucose levels and a significant reduction of insulin dosage in patients suffering from poorly-controlled type 2 diabetes. Conclusion: Modified short-term dietary oatmeal interventions are an effective and economical tool in the treatment of patients suffering from poorly-controlled type 2 diabetes.